Implementation of Criminal Law in Narcotics Cases in Indonesia - Clarissa (PT. Anagata Sembagi Education, 2024)
Issues related to drug-related crimes have become a major concern around the world and an ongoing topic of discussion at the national and international levels. The problem of drug abuse is not only a national, but also a global challenge that is troubling various nations. The adverse effects of drug abuse involve damage to physical, mental health, emotional, and societal values. Narcotics abuse has become a serious threat faced by society and the nation, forming a national and international organized crime. With this background, it raises a topic entitled